Efficacy of custom made oral appliance for treatment of obstructive sleep apnea - V R Cilil; N K Sapana Varma; Siby Gopinath; V V Ajith (Wolters Kluwer Medknow Publications, 2015)
Introduction: oral appliance for the treatment of OSA is considered as an effective, low-risk alternative to CPAP. Demand for oral appliance increases as an alternative for those who cannot tolerate CPAP and refuse surgery. Oral appliances uses the traditional methods to advance the mandible thus modify the posture and their by enlarge the airway or otherwise reduce the collapsibility. Aims and Objectives: The main objective of this study was to evaluate the efficacy of custom made oral appliance on sleep characteristics of OSA patients. Materials and Methods: Polysomnography was done on 15 patients of 24-60 years of age before (T1), and after the delivery of the custom made oral appliance (T2). Statistical Analysis: Paired t tests were performed to determine the significance of change in the polysomnographic and cephalometric variables. P < 0.05 was considered as significant. Results: All patients with oral appliance showed an improvement in sleep parameters with an increase in sleep efficiency, and desaturation index with the use of oral appliance. ESS and cephalometric findings showed improvement in the sleep apnea in concordance with the sleep parameters. Conclusions: Custom made oral appliance is a useful treatment option for improving quality of sleep and can be considered as an alternative treatment modality.